Endogenous tumor necrosis factor alpha is required for enhanced antimicrobial activity against Toxoplasma gondii and Listeria monocytogenes in recombinant gamma interferon-treated mice. - Langermans, J A (1992)
In vitro studies have shown that macrophages stimulated with recombinant gamma interferon (rIFN-gamma) produce tumor necrosis factor alpha (TNF-alpha), which in an autocrine fashion activates these cells. The aim of the present study was to determine whether endogenously formed TNF-alpha also is required for rIFN-gamma-induced macrophage activation and enhanced antimicrobial activity in vivo. After an intraperitoneal injection of rIFN-gamma into CBA/J mice, their peritoneal macrophages released enhanced amounts of NO2- and inhibited the intracellular proliferation of Toxoplasma gondii. Injection of neutralizing antibodies against TNF-alpha simultaneously with the rIFN-gamma completely inhibited both the release of NO2- by macrophages and their toxoplasmastatic activity. Similar results were observed after intraperitoneal injection of a competitive inhibitor of L-arginine, NG-monomethyl-L-arginine, together with rIFN-gamma, demonstrating that in vivo L-arginine-derived reactive nitrogen intermediates are essential for the induction of toxoplasmastatic activity. Intravenous injection of rIFN-gamma inhibited the growth of Listeria monocytogenes in the livers and spleens of mice; this effect was abrogated by antibodies against TNF-alpha. Intravenous injection of a large dose of rTNF-alpha resulted in a decrease in the number of bacteria in the liver and spleen, but an injection of rIFN-gamma and rTNF-alpha did not result in enhanced inhibition of the proliferation of L. monocytogenes. Together, the results of the present study are the first to demonstrate that endogenous TNF-alpha is required in vivo for the expression of macrophage activation with respect to the release of reactive nitrogen intermediates and toxoplasmastatic activity and for enhanced listericidal activity in the livers and spleens of mice stimulated with rIFN-gamma.